EFEKTIFITAS PENERAPAN MODEL PEMBELAJARAN GROUP INVESTIGATION (GI) DALAM MENUMBUHKAN PERILAKU KOOPERATIF - Kurniyatul Faizzah (LPPM IAI IBRAHIMY GENTENG BANYUWANGI, 2015)
Nowadays activities in learning process in a classroom have changed into a character building orientated learning process which was before it was an individual oriented learning process. Value of cooperation among classmates soon will be neglected during the learning process. The implementation of Group Investigation learning model becomes an alternative learning model which is effective for inculcating the value of cooperation in performing learning activities aimed to familiarize students to be able to well cooperate with other people and to instill sensitivity of students to help and care of others as well.. This model gives students theextend of opportunity to take part actively in learning process since the planning process until the way of learn some topic through investigation tehnic. The implementation of Group Investigation Model is based on the combination of some theories, which are constructivism, democratic teaching, and the group of cooperative learning. Based on constructivism views, the implementation of the Group Investigation Model gives students the extend of opportunity to take part actively in learning process. Democratic teaching is a learning process which is based on democratic value. Based on the views, the Group Investigation Model is believed to be effective to instill the value of cooperation in every student’s activity.